Ketimpangan, Pola Spasial, dan Kinerja Pembangunan Wilayah di Provinsi Jawa Timur - Mohammad Reza Fauzi; Ernan Rustiadi; Sri Mulatsih (P4W LPPM IPB, 2019)
Disparity, Spatial Pattern, and Performance of Regional Development in East Java Province Development is a multidimensional process that aims to generate significant changes in the betterment of people's lives. However, development does not always able to form regional balance. The phenomenon of disparity always shades the regional development process. As a province with the highest number of regencies and cities, the development of East Java Province is inseparable from the phenomenon of disparity. This study aimed to analyze the performance, regional disparities, and spatial autocorrelation of regional development in East Java Province in 2017. Performance of regional development was measured using TOPSIS analysis. Level of regional disparity was calculated by the Coefficient Variation (CV). Spatial pattern of development performance was explored through analysis of spatial autocorrelation by Moran Index and Local Indicator of Spatial Autocorrelation (LISA). Results of analysis on regional development performance show that Kediri City had the highest performance in East Java Province, meanwhile Tuban Regency had the lowest performance. At the regional level, Pantura (North Coast) and Central Region have higher regional development performance average compared to Pansela (South Coast), Tapal Kuda, and Madura regions. Regional disparity in East Java Province occur between regions and within regions (between regencies/cities). Pantura is the region with the highest regional development performance disparity, meanwhile Madura region is relatively homogenous with low development performance. Result of Moran and LISA analysis interpret that spatial and contiguity aspects effect regional development significantly which tends to form a cluster pattern. Therefore, spatial factors and regional linkage are essential elements in regional development.